Study of the fatigue behaviour of dissimilar aluminium joints produced by friction stir welding. (January 2016) - Infante, V.; Braga, D.F.O.; Duarte, F.; Moreira, P.M.G.; de Freitas, M.; de Castro, P.M.S.T.
Highlights: The study compares the experimental behaviour with three different finite element models. Fatigue tests of welded joints show low fatigue strength in comparison with base materials. Fatigue performance of dissimilar joints suggests a shallower S–N curve than for similar joints. Abstract: Building lightweight structures is one of the key strategies to guarantee an efficient, competitive, safe and sustainable public transport system. The implementation of reliable and optimized lightweight structures needs to achieve high levels of performance, cost effectiveness and sustainability. The expected weight saving will significantly reduce fuel consumption and therefore CO2 emission per passenger-kilometer. Friction Stir Welding (FSW) is a solid state process enabling to develop new design concepts for lightweight metallic materials, where previously conventional manufacturing processes as riveting or classical welding were used. This study was conducted within the LighTRAIN project that aims to improve the life cycle costs of the underframe of a passenger railway car, with a novel lightweighted solution. The major objective of the research was to study the fatigue behaviour of dissimilar welded joints based on two different aluminium alloys: AA6082 and AA5754. The paper presents the experimental results obtained in two different structures: AA6082-T6 2 mm and AA5754-H111 2 mm thick joints, and AA6082-T6 2 mm thick joints. Fatigue tests were carried out on lap joints specimens with a constant amplitude loading with a stress ratio R = 0.1. The results of the fatigue tests are presented as well as detailed metallographic characterization of the weld zone and also the hardness distribution at the weld region. Fatigue tests performed on similar and dissimilar joints show low fatigue strength when compared with base materials AA5754 and AA6082, which is associated with the typical "hook" defect inherent to this welding process. The fatigue performance of AA6082 and AA5754 FSW welded joints suggests a shallower S–N curve than for the similar AA6082 FSW welded joints with an improvement in fatigue performance for lower applied stress ranges.